Reflections on gender transformative approaches in agriculture - The promise and cautionary tales - Wong, Franz; Pyburn, Rhiannon (CGIAR Collaborative Platform on Gender Research, 2019)
Presented by Franz Wong (KIT Royal Tropical Institute) and Rhiannon Pyburn (CGIAR Collaborative Platform for Gender Research) on 20 June 2019, as part of the webinar 'Reflections on gender transformative approaches in agriculture - The promise and cautionary tales'. The webinar was co-organized by the CGIAR Collaborative Platform for Gender Research and KIT Royal Tropical Institute.